2022
DOI: 10.2355/isijinternational.isijint-2021-472
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics Analysis of Steam Reforming of Methane on Sponge Iron

Abstract: The kinetics of steam reforming of methane catalyzed by sponge iron was studied at temperatures between 875°C and 1 050°C. Results shows that sponge iron acts as a catalyst and methane conversion is increased in higher temperatures and with a higher H 2 /H 2 O ratio in the inlet gas. A kinetic model based on chemical reaction control fits well the experimental data up to methane conversion of 0.5 with an apparent activation energy of 258 kJ/mol. Pore diffusion limits the reaction rate more intensely at higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[10] For these reasons, the most available models in the literature take into consideration the reduction through a gas mixture of hydrogen and carbon monoxide in order to simplify the thermochemical and thermophysical phenomena involved in the process development. [11,12] In the direct reduction process, the reducing agent converts the iron ore to elemental iron directly. The final product is directly reduced iron (DRI) including matrix elements from the ore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] For these reasons, the most available models in the literature take into consideration the reduction through a gas mixture of hydrogen and carbon monoxide in order to simplify the thermochemical and thermophysical phenomena involved in the process development. [11,12] In the direct reduction process, the reducing agent converts the iron ore to elemental iron directly. The final product is directly reduced iron (DRI) including matrix elements from the ore.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the most available models in the literature take into consideration the reduction through a gas mixture of hydrogen and carbon monoxide in order to simplify the thermochemical and thermophysical phenomena involved in the process development. [ 11,12 ]…”
Section: Introductionmentioning
confidence: 99%
“…The composition data on the raw materials to be fed are needed for this analysis. The compositions of the DRI 5,32,33) , coke 34,35) , limestone 36) , and steel scrap 37,38) used in this study are shown in Table 6. The quality of low-P DRI and high-P DRI are compared in Table 7.…”
Section: Analytical Model Description 1 Setting Up the Templatementioning
confidence: 99%
“…The quality of low-P DRI and high-P DRI are compared in Table 7. The composition of Low-P DRI was estimated from that of the iron ore pellet 32) , assuming that the 95mass% of total Fe is reduced to metallic iron and the carbon content of DRI is 1 mass% 5) . The composition of high-P DRI was estimated from that of the iron ore containing P at high content 33) , assuming that the fraction of the metallic iron and the mass concentration ratio of CaO to SiO2 are the same as those of low-P DRI and the carbon content is 0.…”
Section: Analytical Model Description 1 Setting Up the Templatementioning
confidence: 99%
“…For these reasons, the most available models in the literature take into consideration the reduction through a gas mixture of hydrogen and carbon monoxide in order to simplify the thermo-chemical and thermo-physical phenomena involved in the process development [13,14].…”
Section: Introductionmentioning
confidence: 99%